Induction of cell cycle arrest and apoptosis by tomentosin in hepatocellular carcinoma HepG2 and Huh7 cells. (February 2021) - Yu, SH; Lee, CM; Ha, SH; Lee, J; Jang, KY; Park, SH
Tomentosin, a sesquiterpene lactone, is known to possess various biological activities. However, its anticarcinogenic activity against human hepatocellular carcinoma (HCC) cells has not been investigated in detail. Thus, this study aimed to elucidate the cytotoxic mechanism of tomentosin in human HCC cell lines HepG2 and Huh7. WST-1, cell counting, and colony formation assay results showed that treatment with tomentosin decreased the viability and suppressed the proliferation rate of HepG2 and Huh7 cells in a dose- and time-dependent manner. Cell cycle analysis revealed increased population of cells at the SubG1 and G2/M stage, and decreased population of cells at the G0/1 stage in HepG2 and Huh7 cells treated with tomentosin. Annexin V/propidium iodide double staining and TUNEL assay results showed increased apoptotic cell population and DNA fragmentation in HepG2 and Huh7 cells treated with tomentosin. Western blotting analysis results showed that tomentosin treatment significantly increased the expression level of Bax, Bim (short form), cleaved PARP1, FOXO3, p53, pSer15p53, pSer20p53, pSer46p53, p21, and p27, but decreased the expression of Bcl2, caspase3, caspase7, caspase9, cyclin-dependent kinase 2 (CDK2), CDK4, CDK6, cyclinB1, cyclinD1, cyclinD2, cyclinD3, and cyclinE in a dose-dependent manner. Taken together, this study revealed that tomentosin, which acted through cell cycle arrest and apoptosis, may be a useful therapeutic option against HCC.